Group acceptance sampling plan for re-submitted lots under generalized pareto distribution - Razzaque Mughal, Abdur; Zain, Zakiyah; Aziz, Nazrina (MAXWELL Science Publication, 2015)
In this study, a Group Acceptance Sampling Plan (GASP) for lot resubmitting is developed for situations in which the lifetime of a product follows the generalized Pareto distribution.The design parameters such as minimum group size and acceptance number are observed when the consumer’s risk, number of testers and the test termination time are pre-specified. The proposed plan requires less sample size than the ordinary GASP.The condition of lot re-sampling was examined and measurement of a resubmitted method having a GASP for inspection.